Determinantes biológicos da comorbidade dos ataques de pânico com depressão e ansiedade de separação - Santos, Jeyce Willig Quintino dos (2011)
Aim: The DPAG has been proposed as an important substrate of panic attacks. Clinical data suggest that childhood separation anxiety and depression predispose panic attacks. Accordingly, the present study examined the effects of mother separation (MS, a model of childhood separation anxiety), learned helplessness (LH, a model of dysthimic or reactive depression) and olfactory bulbectomy (BOX, a model of endogenous depression) on the thresholds of defensive behaviors induced by electrical stimulation of DPAG of adult rats. Rat performance was also evaluated in the forced swim test (FST) in all groups, in the elevated plus-maze (EPM) in MS and LH groups, and in elevated T-maze (ETM) and open-field (OF) in BOX group. Methods: BOX: Young male Wistar rats (P40) were either bulbectomized (BOX, n = 22) or sham operated (RFO, n = 28). Rats were implanted with electrodes in the DPAG in P60 and, 5 days after that, stimulated with stepwise increasing senoidal pulses (0-60 µA; 60 Hz, 30 s) in steps of 5 µA up to the production of galloping or jumping responses. Next, they were tested in the OF (P66), ETM (P67) and FST (P68). Defensive behaviors were examined through threshold logistic analysis and compared by likelihood ratio chi-square tests for P<0.05. LTE avoidance responses were analysed by repeated measures ANOVA followed by Bonferroni’s t-tests. OF, FST and LTE escape responses were evaluated by Student’s t-test for independent samples. LH: Male adult Wistar rats were kept in individual cages in a controlled environment as described. The DPAG of rats was stimulated as described 5 days after the electrode implantation. Rats which presented gallops 7 with currents below 60 µA were subjected to LH yoked training of one-way shuttle-box escape throughout a 7-day period. LH training sessions consisted of the presentation of 30 footshocks (1 mA, 30 s duration,1 min interval), either escapable (ES, n=23) or inescapable (IS, n=23), to control and LH rats, respectively. The escape learning deficit was examined the day after the training period in a new task of two-way shuttle-box escape (test-session). Thresholds of DPAG-induced defensive responses of both groups were reexamined 1 and 6 days after the test-session. Next, rats were tested in the EPM and FST. Responses were analysed as described. MS: Nulliparous pregnant Wistar rats were kept in a temperature- (23ºC) and light-controlled room (12 x 12 h light-dark cycle). The day after parturition (P1), female pups were sacrificed and males (4 to 8 per litter) were kept with their dams up to the weaning day (P21). The MS (3 h/day) was carried out at morning throughout the lactation period. During MS, rats were moved to new boxes in which mother deprived rats (MDR, n=39) remained alone and non-deprived rats (NDR, n=30) were kept with their dams. DPAG electrodes were implanted in P60 and thresholds of DPAG-induced defensive responses were recorded in P65. Next, the rats were tested in the EPM and FST. Responses were analysed as above described. Results: BOX: Compared with sham-operated rats, BOX rat thresholds were lower for the DPAG-evoked responses of exophthalmus (∆I50% = I50% -32%, P <0.001), immobility (∆I50% = I50% -18%, P <0.05) , trotting (∆I50% = I50% -22%, P <0.005), galloping (∆I50% = I50% -14%, P <0.005) and jumping (∆I50% = I50% -19%, P <0.005). Bulbectomy produced depression-like responses in the FST. On the other hand, although the bulbectomy reduced the exploration of the central area of OF, thereby suggesting an increase in anxiety, 8 LTE avoidance anxiety-like responses did not change. Thus, BOX rats presented opposite effects on panic-like escape responses of LTE and DPAG, which were either attenuated or facilitated, respectively. LH: IS and ES groups presented baseline thresholds virtually identical for all responses except jumping. Compared to ES group, IS rats showed significant deficits in escape performance in test-sessions. Moreover, whereas the LH produced only a moderate attenuation of DPAG-evoked defensive responses the day after the test-session, responses were markedly attenuated 6 days after that for immobility (∆I50% = 22%, P<0.001), trotting (∆I50% = 28%, P<0.0001) and galloping (∆I50% = 29%, P<0.0001). The FST confirmed pro-depressive effects of LH and the LCE test showed a mild anxiolytic trend. MS: Compared to controls, MS rats showed a marked reduction in the thresholds of immobility (∆I50% = -20%, P<0.0001), exophthalmus (∆I50% = -28%, P<0.0001), trotting (∆I50% = -17%, P<0.0001), galloping (∆I50% = -20%, P<0.0001) and jumping (∆I50% = -13%, P<0.005). There was no difference between groups in LCE and forced swimming tests. Conclusions: MS and LH have opposite effects on DPAG-evoked somatic defensive responses, either facilitating or inhibiting, respectively. Thus, whereas the present results support the predisposing influence of childhood separation anxiety in panic attacks, they do not support the facilitatory effect of acute depressive states. Otherwise, the effects of olfactory bulbectomy support the predisposing influences of endogenous depression in panic attacks. Support: AFIP, FAPES.